Effect of heparin reversal by protamine sulfate on the outcome of thrombolysis in acute ischemic stroke after percutaneous coronary intervention - Khaled Elmancy; Hany Aref; Nevine El Nahas; Azza Abd ElNasser Abd ElAziz; Ayman Hassan El-Sudany; Hossam Shokri; Emad Effat Fakhry; Ahmed Elbassiouny; Fatma Fathalla Kenawy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Acute ischemic stroke (AIS) after percutaneous cardiac intervention (PCI) is an uncommon complication, ranging from 0.1% to 0.4% according to recent incident reports. It is associated with significantly increased risks of both in-hospital mortality and major adverse cardiovascular events. (MACEs). Although intravenous thrombolysis (IVT) is the recommended standard for the management of AIS in the first 4.5 h after stroke onset, it is contraindicated in this subgroup of AIS patients who receive heparin and usually have a partial thromboplastin time (PTT) of more than 40 s. Fortunately, protamine sulfate is an effective antidote that can counteract the anticoagulant effect of heparin within 5 min. This work aimed to assess the safety and efficacy of IVT in acute ischemic stroke patients after PCI and after the reversal of the heparin effect by protamine sulfate. The total number of patients who developed AIS after PCI was 42, all of whom received loading antiplatelet agents before PCI. The patients were randomly assigned to two groups: group I received heparin reversal via intravenous protamine sulfate, and group II was conservatively followed up. Results While group I showed significantly less stroke severity on discharge and better outcomes at 3 months, there was no significant difference between the groups in terms of mortality rates or bleeding events. Conclusion IVT after heparin reversal by protamine in appropriately selected AIS patients is thought to have a good outcome without increasing the risk of symptomatic ICH.